Heat-Related Training and Educational Material Needs among Oil Spill Cleanup Responders - Brenda L Jacklitsch; Keith A King; Rebecca A Vidourek; Ashley L Merianos (SAGE Publishing, 2018)
Heat-related illness (HRI), injury, and death among oil spill cleanup responders can be prevented through training and educational materials. This study assessed heat-related training and educational materials currently used and desired by oil spill cleanup responders. A needs assessment was completed by 65 oil spill cleanup responders regarding their occupational heat-related experiences and training needs. Oil spill cleanup responders reported participating on average in 37 oil spill cleanup activities per year. Most reported experiencing additional HRI risk factors, such as high temperatures and humidity and wearing personal protective equipment and clothing ensembles, respirators, and personal flotation devices. Many reported experiencing symptoms of HRI (profuse sweating, headache, weakness, decreased urine output, high body temperatures) and experiencing heat exhaustion. Although multiple prevention controls were reported, only 1 in 4 reported using an acclimatization plan. The most common training delivery method and education received included just-in-time training and printed materials. The most desirable future training delivery methods and education products were smartphone or tablet applications, printed materials, and online training. Findings from this study may be beneficial to safety and health professionals and health educators, particularly those interested in developing heat stress training and educational materials for oil spill cleanup responders.